A Liouville comparison principle for solutions to semilinear parabolic second-order partial differential inequalities in the whole space - Kurta, V.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
We obtain a new Liouville comparison principle for weak solutions (u,v) to semilinear parabolic second-order partial differential inequalities of the form